A Bibliometric Analysis of Supply Chain Management Research from the Perspective of Social Network. Issue 2 (3rd April 2019) - Ye, Yong
ABSTRACT: The research mainly aims at the hotspot of supply chain management from the perspective of a social network by drawing knowledge mapping and provides the visualization reference in this research field. Firstly, it collects the literature data of the core database of Web of Science from 2003 to 2018. Then it uses the literature co-occurrence method, knowledge mapping method, and content analysis method, and analyzes the current situation of supply chain management under the perspective of social network. It also applies Citespace software and bibliographic co-existing analysis system to analyze the literature cooperation network and topic in this field. Results showed that there are three important research angles, including the analysis of supply chain network members of the supply chain and the construction of sustainable supply chain network. Based on the knowledge mapping, this study is still relatively macro and cannot cover all areas of supply chain management. This study only investigated the state of correlational research in WOS and Google Trends and not additional databases. However, the research on dynamic network relationship and structure measurement is still lacking.